2017
DOI: 10.1111/jphp.12613
|View full text |Cite
|
Sign up to set email alerts
|

Relative bioavailability of coenzyme Q10 formulation for paediatric individualized therapy

Abstract: The results obtained showed that liquid emulsion improves the bioavailability of CoQ10 respect to solid form which not only facilitates the individualized administration for the child but in turn could increase the therapeutic efficacy, which should be confirmed by further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In view of their superior absorption, the use of gel and oil based formulations of CoQ10 have been recommended in preference to tablets in the treatment of patients with mitochondrial disease (Weis et al, 1994) . Recently, a study by Martinefski et al (2017) reported that soft gel formulations improved the bioavailability of CoQ10 with respect to solid formulations.…”
Section: Coq10mentioning
confidence: 99%
“…In view of their superior absorption, the use of gel and oil based formulations of CoQ10 have been recommended in preference to tablets in the treatment of patients with mitochondrial disease (Weis et al, 1994) . Recently, a study by Martinefski et al (2017) reported that soft gel formulations improved the bioavailability of CoQ10 with respect to solid formulations.…”
Section: Coq10mentioning
confidence: 99%
“…Currently, there is considerable debate as to whether formulations of ubiquinol rather than the ubiquinone form of CoQ 10 have a better absorption from the gastrointestinal tract (GI). It has been reported that absorption of ubiquinol is three to four times higher than CoQ 10 in the GI [91,92]. However, because during absorption in the GI CoQ 10 undergoes reduction to ubiquinol, the suggested increased bioavailability of the ubiquinol formulations may be due to the matrix in which the ubiquinol is held in rather than its redox state.…”
Section: Coq 10 Limitations In Etc Disordersmentioning
confidence: 99%
“…In light of their increased absorption, the use of both gel and oil-based formulations has been recommended over the use of conventional tablet formulations in patients with ETC disorders [90]. In a study by Martinefski, Samassa [91] it was reported that liquid emulsion improved the bioavailability of CoQ 10 with respect to solid formulations. Currently, there is considerable debate as to whether formulations of ubiquinol rather than the ubiquinone form of CoQ 10 have a better absorption from the gastrointestinal tract (GI).…”
Section: Coq 10 Limitations In Etc Disordersmentioning
confidence: 99%
“…Even though supplementation with CoQ 10 is beneficial in both primary and secondary deficiencies, the design of oral formulations containing CoQ 10 has become a challenge. CoQ 10 shows very low solubility in water because of their high lipophilicity and molecular weight [ 7 , 8 ]. The low CoQ 10 apparent density is another major disadvantage for the development of oral forms, especially to satisfy daily high-dose (50 mg/Kg/day) regimens in the treatment of adult patients with the deficiency, who also suffer from dysphagia as another secondary neurological consequence.…”
Section: Introductionmentioning
confidence: 99%